Splitting, impulsivity, and intimate partnerships in young obese women seeking bariatric treatment - Zmolikova J (Dove Medical Press, 2016)
Jana Zmolikova,1,2 Dita Pichlerova,3 Petr Bob,1,4 Denisa Schückova,5 Jitka Herlesova,3 Petr Weiss6 1Department of Psychiatry, First Faculty of Medicine, Center for Neuropsychiatric Research of Traumatic Stress, Charles University, 2Department of Clinical Psychology, Na Homolce Hospital, 3OB Clinic, Prague, 4Faculty of Medicine, Central European Institute of Technology, Masaryk University, Brno, 5Iscare Clinical Centre, 6Institute of Sexology, First Faculty of Medicine, Charles University, Prague, Czech Republic Background: Splitting represents a defense mechanism that describes fragmentation of conscious experience that may occur in various psychopathological conditions. The purpose of this study was to examine the relationship of splitting with disturbed cognitive and affective functions related to impulsivity and intimate partnerships in a group of obese patients indicated for bariatric treatment and compare the results with other obese patients and patients with bulimia nervosa. Methods: In this clinical study, we assessed 102 young women. The sample was divided into three subgroups: obese women (N=30), obese women indicated for bariatric treatment (N=48), and patients with bulimia nervosa (N=24). The patients were assessed using Splitting Index and Barratt Impulsivity Scale, and selected information about their intimate partnership was documented for all the participants.Results: The main results of this study indicate significant differences in the relationship of splitting and impulsivity with difficulties in intimate partnerships. These differences discriminate obese patients indicated for bariatric treatment from other obese patients and patients with bulimia nervosa.Conclusion: These findings may have significant implications for treatment of the obese patients indicated for bariatric treatment and their presurgery psychological evaluations. Keywords: splitting, impulsivity, obesity, bulimia nervosa, bariatric treatment